Analysis of the efficacy of splenic artery superselective embolization in cirrhosis with hepatocellular carcinoma - Ke Zhao; Hong-Tao Hu; Hai-Liang Li; Hong-Tao Cheng; Ya-nan Zhao; Yuan Hang; Quan-jun Yao (PLoS ONE, 2025)
Background To explore the safety and effectiveness of partial splenic embolization (PSE) in patients with hypersplenism and hepatocellular carcinoma (HCC) and to compare the efficacy of superselective and non-superselective embolization of splenic artery branches. Procedure We retrospectively analyzed 64 patients with HCC who underwent PSE between August 2020 and December 2022. The patients were categorized into two groups based on different treatment plans: Group A (n=33) underwent superselective embolization and Group B (n=31) underwent non-superselective embolization of the splenic artery branches. The safety and effectiveness of the two methods were evaluated along with changes in peripheral blood cells [mainly white blood cells (WBC) and red blood cells (RBC)] and platelet (PLT) counts at different time points after PSE. Postoperative adverse events were also compared between the two groups, Results The technical success rate was 100% for both procedures. The PLT and WBC counts of the two groups significantly increased one week after PSE (P<0.05), and there was no statistically significant difference in the RBC count changes. At follow-up (4, 16, and 24 weeks), the PLT and WBC counts remained consistent at levels which were significantly different from those before PSE (P<0.05). However, the RBC counts were not significantly different (P>0.05). An independent sample t-test was used to compare the differences in blood counts between the two groups at the same time point. There were no statistically significant differences in PLT, WBC, and RBC counts between Group A and Group B at any time point after PSE (P>0.05). The incidence of fever and pain in Group B was significantly higher than that in Group A (P<0.05), Conclusion Partial splenic artery embolization is a safe and effective treatment option for hypersplenism. Both splenic artery branch superselective and non-superselective embolization strategies demonstrated comparable outcomes. However, superselective embolization exhibited a lower incidence of postprocedural complications than non-superselective embolization.